2013
DOI: 10.1242/jcs.116293
|View full text |Cite
|
Sign up to set email alerts
|

COUP-TFII orchestrates venous and lymphatic endothelial identity by homo- or hetero-dimerisation with PROX1

Abstract: SummaryEndothelial cell (EC) identity is in part genetically predetermined. Transcription factor NR2F2 (also known as chicken ovalbumin upstream promoter transcription factor II, COUP-TFII) plays a key role in EC fate decision making; however, many of the underlying mechanisms remain enigmatic. In the present study, we demonstrate that NR2F2 differentially regulates gene expression of venous versus lymphatic ECs (LECs) and document a novel paradigm whereby NR2F2 homodimers induce a venous EC fate, while hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 42 publications
6
58
0
1
Order By: Relevance
“…NR2F2 binds to the regulatory motif that is also bound by NR2F1 and HNF4A, but the mRNA expression in this system makes clear that NR2F2 is the crucial factor here and that it likely acts as a repressor (see ismara.unibas.ch/supp/dataset3/ismara_report/pages/HNF4A_NR2F1,2.p2). NR2F2 (also known as COUP-TFII) is known to play a crucial role in lymph vessel differentiation [48] and has recently been reported to, in a different context, regulate genes involved in inflammation [49]. These observations together are consistent with ARMADA's prediction that NR2F2 plays an important role in the inflammatory response in HUVEC cells.…”
Section: Resultssupporting
confidence: 71%
“…NR2F2 binds to the regulatory motif that is also bound by NR2F1 and HNF4A, but the mRNA expression in this system makes clear that NR2F2 is the crucial factor here and that it likely acts as a repressor (see ismara.unibas.ch/supp/dataset3/ismara_report/pages/HNF4A_NR2F1,2.p2). NR2F2 (also known as COUP-TFII) is known to play a crucial role in lymph vessel differentiation [48] and has recently been reported to, in a different context, regulate genes involved in inflammation [49]. These observations together are consistent with ARMADA's prediction that NR2F2 plays an important role in the inflammatory response in HUVEC cells.…”
Section: Resultssupporting
confidence: 71%
“…Coup-TFII also activates Nrp-2, although it is currently unknown whether this is via the Coup-TFII/ Prox1 complex (Lin et al 2010). Alternatively, it could then be argued that the Coup-TFII/Prox1 protein complex might regulate the expression of additional LEC-specific genes such as Hey1/2, as recently reported (Aranguren et al 2013), and these genes in turn inhibit Vegfr3 expression. We found that the Prox1-Vegfr3 feedback loop is operational in not only LEC progenitors but also differentiating LECs at least until E13.5.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, we determined that the autoregulation of Prox1 expression is dose-dependent, and the number of Prox1-expressing LEC progenitors in the CV of Prox1 +/À mice is reduced due to the decreased amount of available Coup-TFII/Prox1 protein complex during the early stages of Prox1 regulation in these cells (Srinivasan and Oliver 2011). This protein complex is known to regulate several LEC-specific genes, including the lymphangiogenic receptor tyrosine kinase Vegfr3 (Lee et al 2009;Yamazaki et al 2009;Aranguren et al 2013).…”
mentioning
confidence: 99%
“…[43][44][45] More recently, it was found that lymphatics express COUP-TFII as well and that COUP-TFII heterodimerization with Prox1 transcription factor is essential for lymphatic specification. 46,47 You et al 45 elegantly demonstrated that COUP-TFII plays a cell autonomous role in venous specification. Venous endothelial cells lacking COUP-TFII display a partial reduction of venous markers but a strong upregulation of several arterial markers.…”
Section: Corada Et Al Specification Of Arteries and Veins 2375mentioning
confidence: 99%